Comparative Feeding Performance and Digestive Physiology of Helicoverpa armigera (Lepidoptera: Noctuidae) Larvae-Fed 11 Corn Hybrids. Issue 1 (16th February 2015) - Hosseininejad, A. S.; Naseri, B.; Razmjou, J.
Abstract : This study aimed to evaluate the feeding responses and digestive proteolytic and amylolytic activity of Helicoverpa armigera (Hübner) on 11 corn ( Zea mays L.) hybrids at 25 ± 1°C, 65 ± 5% relative humidity (RH), and a photoperiod of 16:8 (L:D) h. The fourth- and fifth-instar larvae fed on hybrid K47*K19 had the highest weight of food consumption and those reared on hybrid KSC705 had the lowest value of food consumption. The highest weight gain of the larvae was observed when H. armigera were fed hybrid KLM78*MO17 and lowest when they were fed hybrids K36 * MO17, KSC705, and K35 * K36. Pupal weight of H. armigera was heaviest when larvae were fed hybrid K47*K19 and lightest when they were fed hybrid KSC705. The highest proteolytic activity of the fourth-instar larvae was observed when they were fed hybrid KSC705, and the lowest activity was observed when they were fed hybrid K47*A67. Fifth-instar larvae that fed on hybrid K47*K19 showed the highest proteolytic activity. Fourth-instar larvae that fed on hybrid K36*MO17 showed the highest amylase activity. The fifth-instar larvae fed on hybrid K47*A67 showed the maximum amylase activity and those reared on the K48*K18 showed the minimum activity. Our results indicated that K36 * MO17, KSC705, and K48 * K18 were the most unsuitable hybrids for feeding H. armigera .